Integrated management of small reservoirs for multiple uses - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2011)
The V3 project will develop integrated management options of Small Reservoirs (SR) with the objectives of perpetuating infrastructures, protecting/impro- ving water quality for various uses, reaching/en- hancing water productivity potentials in ensuring an equitable allocation of water resources.